2018
DOI: 10.15171/apb.2018.004
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Development of a Cardiac Tissue-Specific and Hypoxia-Inducible Expression Vector

Abstract: Purpose: Cardiovascular gene therapy is a sophisticated approach, thanks to the safety of vectors, stable transgene expression, delivery method, and different layers of the heart. To date, numerous expression vectors have been introduced in biotechnology and biopharmacy industries in relation to genetic manipulation. Despite the rapid growth of these modalities, they must be intelligently designed, addressing the cardiac-specific transgene expression and less side effects. Herein, we conducted a pilot project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…26 (3) Several reports that used CRM did not compare CRM-containing vectors to vectors that differed only in lacking the CRM. [37][38][39]41 In one case, this comparison revealed that addition of a cardiomyocyte-speci c CRM to the cardiac troponin T promoter either had no effect or decreased transgene expression in mouse hearts. 40 (4) When compared to enhancer-promoter combinations that lack identi ed CRMs, CRM-containing vectors have not always yielded the highest levels of expression.…”
Section: Discussionmentioning
confidence: 99%
“…26 (3) Several reports that used CRM did not compare CRM-containing vectors to vectors that differed only in lacking the CRM. [37][38][39]41 In one case, this comparison revealed that addition of a cardiomyocyte-speci c CRM to the cardiac troponin T promoter either had no effect or decreased transgene expression in mouse hearts. 40 (4) When compared to enhancer-promoter combinations that lack identi ed CRMs, CRM-containing vectors have not always yielded the highest levels of expression.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory element mainly boosts the performance of the αMHC promoter. Combined with other (cardiac)-muscle-specific promoters like SPc5-12, cTnT, MLC2v, and SLN, the CS-CRM4 element predominantly increased the specificity of cardiac gene expression [9,36,37,57]. In a large-scale approach, a library comprising 400 bp sequences of potentially cardio-specific enhancer elements was screened for identification of novel enhancer sequences in mouse hearts in vivo using an AAV9-based assay [58].…”
Section: Cardio-specific Enhancersmentioning
confidence: 99%
“…The activity of the CRM in these initial reports was impressive, increasing in vivo transgene expression from plasmids and AAV vectors by up to 200-400-fold and preserving tissue specificity [16][17][18] . However, this early work on CRM-containing vectors from the Chuah/VandenDriessche group and others [28][29][30][31][32][33][34] also revealed limitations: (1) Some of the initially described CRM had no effect or decreased expression when placed upstream of the transthyretin promoter 16 . (2) CRM activity depends both on the identity of the adjacent promoter and on the transgene that is expressed, with up to 10-fold differences in CRM activity depending on the promoter [16][17][18]29 , and similar transgene-dependent variability 18 .…”
Section: Insertion Of the Apoai Gene At The Transcription Start Site ...mentioning
confidence: 99%
“…(2) CRM activity depends both on the identity of the adjacent promoter and on the transgene that is expressed, with up to 10-fold differences in CRM activity depending on the promoter [16][17][18]29 , and similar transgene-dependent variability 18 . (3) Several reports that used CRM did not compare CRM-containing vectors to vectors that differed only in lacking the CRM [29][30][31]33 . In one case, this comparison revealed that addition of a cardiomyocyte-specific CRM to the cardiac troponin T promoter either had no effect or decreased transgene expression in mouse hearts 32 .…”
Section: Insertion Of the Apoai Gene At The Transcription Start Site ...mentioning
confidence: 99%